Ultrasound-guided erector spinae plane block versus trocar site local anesthetic infiltration for laparoscopic colorectal resection: A prospective, randomized study (Annals of Medical Research, 2022)
Aim: Colorectal resection is a procedure that might cause severe pain in the postoperative period. Erector Spinae Plane Block (ESPB) is a interfascial plane block technique used frequently in recent years to provide postoperative analgesia. The study aimed to compare the ESPB and trocar site infiltration on pain scores and postoperative fentanyl consumption in patients undergoing Laparoscopic Colorectal Resection (LCRR).Materials and Methods: ASA I-III, 48 patients scheduled for LCRR were randomly assigned into two groups. Bilateral ultrasound- guided ESPB with 0.25% bupivacaine 20 ml was administered to Group ESPB (n=24) at T7 level on each side. Trocar Site Group (n=24) was injected with peri-incisional 20 ml 0.25% bupivacaine subcutaneously in trocar sites after surgery. Intravenous (iv) dexketoprofen and iv 0.1mg/kg morphine were injected into both groups half an hour before the surgery ended. At the postoperative 12th hour, 50 mg iv dexketoprofen was repeated, and analgesia was achieved with Patient Controlled Analgesia (PCA) with fentanyl. Postoperative pain scores, fentanyl consumption, opioid-related side effects, and need for rescue analgesia were noted.Results: The twenty-four hour fentanyl consumption was significantly lower in the ESPB group than the trocar site group (438.96 ± 297.99 mcg vs. 738.33 ± 247.35 mcg, respectively p=0.001). Compared with the trocar site, the pain scores were statistically higher in the trocar site group during all time period (P < 0.05). Rescue analgesia requirement was statistically higher in the trocar site group than the ESPB group (20/24 vs. 8/24 respectively, p=0.001).Conclusions: ESPB reduced postoperative opioid consumption and pain scores by providing effective analgesia in LCRR.
Keywords: Erector Spinae Plan Block; laparoscopic colorectal resection; oostoperative analgesia